Sub-10 parts per billion detection of hydrogen with floating gate transistors built on semiconducting carbon nanotube film. (15th August 2021) - Zhou, Shaoyuan; Xiao, Mengmeng; Liu, Fangfang; He, Jianping; Lin, Yanxia; Zhang, Zhiyong
Abstract: Semiconducting carbon nanotubes (CNTs) based gas sensors have shown great promise owing to the high sensitivity, low cost and compatible to integrated circuits (ICs), but are not able to detect H2 with sub-10 ppb concentration, which is necessary to leakage monitoring in nuclear power plants. Here, we significantly enhance the limit-of-detection (LOD) and comprehensive performance of CNT based hydrogen sensors mainly through adopting a floating gate (FG) field-effect-transistor (FET) structure. The sensors are constructed by using high-purity semiconducting CNT network film as channel, Pd nanoparticles as H2 -sensitive material, and Y2 O3 dielectric layer between them as gate insulator. The introduction of Y2 O3 film brings a co-optimization of sensitivity, selectivity and stability to CNT film gas sensors through the synergistic amplifying effect and protection effect. Specifically, the fabricated FG FET hydrogen sensors with the optimized Y2 O3 thickness show a record LOD of 90 ppb at room temperature and even down to 5 ppb at ∼100 °C. Compared with conventional resistance-type sensors, the FG FET sensors exhibit more than one magnitude enhancement on response. Furthermore, the FG FET sensors exhibit excellent stability and well compatibility to CNT ICs, and are potential used as an excellent platform to develop smart sensors. Graphical abstract: Image 1